International business negotiation strategies based on bargaining power assessment: the case of attracting investments - Peleckis, Kęstutis (Journal of Business Economics and Management, 2016)
At present business solutions are used for development and implementation of negotiating strategies for international business, which are not universally suitable for business development in all situations in context of globalization, with current challenges, which are characterized by increasing risk, uncertainty and cultural differences. The purpose of the research is to provide a theoretical model for developing and implementing international business negotiation strategies, based on bargaining power assessment, as well as to conduct an experiment and test the suitability and adaptability of the developed model in an international business negotiation situation – in case of attracting investments. Research methods – scientific literature analysis, comparative, logical analysis and synthesis, comparative and generalisation methods, mathematical and statistic data analysis methods. According to the results, the developed model can be used to reinforce international business negotiations and electronic business negotiations, as an independent systemic unit of the negotiation process (a measure that is autonomous or requires only partial intervention of the negotiator).